Proximate Determinates Of Physical Fitness Level Of Reproductive Women In Bangladesh - Roy, Papri Shanchita; Islam, Md Nazrul (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Results of the analysis revealed that women’s age, place of residence, education, working status, occupation and wealth index were the significant proximate determinants of their physical fitness level. The prevalence of underweight decreased and the prevalence of overweight increased with the increase in the age of reproductive women. Fifty-nine percent of adolescent women (aged 15-19 years) were underweight. The level of education was negatively associated with being underweight but positively associated with being overweight or obese. Of 3,472 illiterate women, about 59 percent were underweight, and of 847 higher-educated women, 37% were overweight. The poor women were three times [odds ratio (OR) =3.22, 95% confidence interval (Cl: 2.73-3.81)] more likely to have underweight or malnutrition compared to women of high socioeconomic status, and rural women were slightly (OR=1.10, 95% Cl: 1.00- 1.22) more likely to have underweight or malnutrition than those of urban. The housewives or unemployed women, were almost two times (OR=1.55. 95% Cl: 1.33- 1.80) more likely of being overweight or obese than the w orking w omen. The findings of this macro-level study of public-health issue will help the Government and planners to take sustainable policies for improving the reproductive women's health. Asiat. Soc. Bangladesh, Sci. 40(2): 187-196, December 2014